Impact of the gut microbiome on the atorvastatin-dependent modulation of the serum lipidome. (25th November 2020) - Roessler, J; Zimmermann, F; Schmidt, D; Escher, U; Jasina, A; Heimesaat, M.M; Gast, M; Poller, W; Giral-Arnal, H; Schumann, P; Leistner, D.M; Landmesser, U; et al.
Abstract: Background and aims: The modulation of serum lipids, in particular of the low-density lipoprotein cholesterol (LDL-C), by statins varies between individuals. The mechanisms regulating this interindividual variation are only poorly understood. Here, we investigated the relation between the gut microbiome and the regulatory properties of atorvastatin on the serum lipidome using mice with depleted gut microbiome. Methods: Over a period of 6 weeks, mice (C57BL/6) with either an intact (conventional mice, CONV, n=24) or antibiotic-based depleted gut microbiome (antibiotic treated mice, ABS, n=16) were put on standard chow diet (SCD) or high fat diet (HFD), respectively. During the last 4 weeks of treatment atorvastatin (Ator, 10mg/kg body weight/day) or control vehicle was administered via daily oral gavage. Blood lipids (total cholesterol, VLDL, LDL-C, HDL-C) and serum sphingolipids were compared among the groups. The expressions of hepatic and intestinal genes involved in cholesterol metabolism were analyzed by qRT-PCR. Alterations in the gut microbiota profile of mice with intact gut microbiome were examined using 16S RNA qRT-PCR. Results: In CONV mice, HFD led to significantly increased blood LDL-C levels as compared with SCD (HFD: 36.8±1.4 mg/dl vs. SCD: 22.0±1.8 mg/dl; P<0.01). In CONV mice atorvastatin treatment significantly reduced blood LDL-C levels after HFD, whereas in ABS mice the LDL-C lowering effect of atorvastatin was markedly attenuated (CONV+HFD+Ator: 31.0±1.8 mg/dl vs. ABS+HFD+Ator: 46.4±3 mg/dl; P<0.01). A significant reduction in the abundance of several plasma lipids, in particular sphingolipids and glycerophospholipids upon atorvastatin treatment was observed in CONV mice, but not in ABS mice. The expressions of distinct hepatic and intestinal cholesterol-regulating genes (ldlr, srebp2, pcsk9 and npc1l1) upon atorvastatin treatment were significantly altered in gut microbiota depleted mice. In response to HFD a decrease in the relative abundance of the bacterial phyla Bacteroides and an increase in the relative abundance of Firmicutes was observed. The altered ratio between Bacteroides and Firmicutes in HFD fed mice was partly reversed upon atorvastatin treatment. Conclusions: Our findings indicate a crucial role of the gut microbiome for the regulatory properties of atorvastatin on the serum lipidome and, in turn, support a critical impact of atorvastatin on the gut microbial composition. The results provide novel insights into potential microbiota related mechanisms underlying interindividual variation in modulation of the serum lipidome by statins, given interindividual differences in microbiome composition and function. Funding Acknowledgement: Type of funding source: Foundation. Main funding source(s): German Heart Research Foundation